Evasion strategies by politicians in news interviews / Nur Zahraa Hanafe - Nur Zahraa , Hanafe (2016)
This research is a comparative study of evasion practices between Prime Minister Dato’ Seri Najib Abdul Razak (Malaysian politician) and President Barack Obama (American politician) in selected news interviews. For each evasive answer given by the politicians, the researcher adapted Clayman’s (2001) framework of evasion in determining the level of evasion and exploring how the politicians evaded questions by using specific strategies. In order to analyze the data, the researcher used the Conversational Analysis (CA) approach to see how the turn-taking of the participants was organized in the news interviews as they asked and answered questions. The main data consists of four political news interviews, two with Prime Minister Najib Razak and two with President Barack Obama. The videos of the news interview were downloaded from the YouTube website and together they lasted for approximately 110 minutes. The topics discussed in the news interviews with both the politicians differed due to the different national and international issues they were dealing with. The findings of the research showed that both politicians practiced evasion in the news interviews at different levels. President Barack Obama from the U.S. evaded the questions at three levels according to Clayman’s (2001) framework of evasion. The levels include full evasion, substantial evasion, and medium-level evasion. Whereas the Malaysian politician, Prime Minister Najib Razak, evaded the questions from interviewers using substantial and medium-level evasions. In addition, the findings also showed how politicians evade answering in news interviews by applying various evasion strategies. Prime Minister Najib Razak used various strategies to evade including anaphoric pronoun, operating on the question, justifying shift, and subversive word repeat. Whereas President Barack Obama used strategies such as justifying shift, minimizing the divergence, token request for permission, anaphoric pronoun, and operating on the question. Surprisingly, all of these strategies were applied in both covert and overt ways by the politicians. Furthermore, the findings also revealed other evasion strategies applied by the politicians in this study that are not included in Clayman’s (2001) framework of evasion. The strategies include generalization in language, hedging, declining to answer, address term, and overlapping utterance. Based on the frequency of the strategies used, the findings revealed that the evasion practiced by Prime Minister Najib Razak is deemed to be more covert in nature as compared to the evasion of President Barack Obama.